An Approach for Examining Alternatives Attributable to Locational Uncertainty. (February 2014) - Murray, Alan T; Wei, Ran; Grubesic, Tony H
The in situ effects of planning and policy often go unnoticed, but their impacts are broad ranging, influencing the social, cultural, economic, and environmental fabric of a community every day. Challenges to planning and policy processes include an enormous range of uncertainties, obfuscating our understanding of an issue and making positive change more difficult to achieve. In this paper we review uncertainty in the context of planning and policy with the intent of illustrating how approaches based on certainty are actually less than definitive. Empirical results derived for three case studies are used to characterize the potential impacts of locational uncertainty on the planning and policy-development process. Two things are evident from the presented results. First, it is possible to conceive of planning models that explicitly account for inherent uncertainties. Second, uncertainty impacts both aggregate findings as well as spatial configuration, but uncertainty can be mitigated, allowing planners, decision makers, government officials, and the public the flexibility to work within a probabilistic continuum that characterizes what is known and unknown. This paper is noteworthy because it illustrates the impacts of locational uncertainty propagating through planning and policy analysis, and provides quantifiable evidence of its significance.